PENGARUH VARIASI PENAMBAHAN SEMEN DAN PERBEDAAN SUHU SAAT PENCAMPURAN TERHADAP MUTU BETON - Doni Rinaldi Basri; Al Hafis Liontin; Muhammad Yazid (Racic : Rab Construction Research, 2023)
Concrete is one of the building structural elements consisting of a mixture of aggregate as a filler and cement paste as a binder. Improving the quality of the concrete mixture will produce concrete with high or maximum compressive strength. Many people think and assume that the more cement used in a concrete mix, the quality/strength will increase. Actually, this assumption is not completely wrong and not completely correct and here the author will try to examine whether adding a lot of cement will improve the quality of the concrete and see the effect of temperature on the quality of the concrete mixture. Variations in adding cement from 450 kg, 500 kg, and 550 kg showed an increase in concrete quality, with compressive strength values of 34.19 MPa, 37.40MPa, and 42.01MPa, while variations in adding 600kg cement experienced a decrease in concrete quality. With a compressive strength value of 41.16MPa. From this research, adding cement does not always improve the quality of concrete. Variations in adding cement of 450kg, 500kg, 550kg and 600kg during morning mixing with a mixing temperature of 24°C with compressive strength values of 33.22 MPa, 37.3MPa, 40.51MPa and 44.69MPa, show increasing quality values. Meanwhile, during the afternoon mixing time with a mixing temperature of 32℃, variations in the addition of 450kg, 500kg and 550kg cement showed that the compressive strength results continued to increase, namely with compressive strength values of 34.19MPa, 37.40MPa and 42.01MPa. Meanwhile, by adding 600 kg of cement variation, the compressive strength value was found to be 41.16MPa, where the concrete experienced a decrease in the compressive strength value. So it can be concluded that mixing the concrete mixture in the morning with a mix temperature of 24℃ is better than in the afternoon with a mix temperature of 32℃